Molecular characterization of novel high-molecular-weight glutenin subunit genes from Aegilops tauschii - Peng, Huijun; Lv, Linlin; Lu, Qiuwen; Zhao, Guojian; Ren, Jiajia; Rehman Arif, Mian Abdur; Su, Yarui; Cheng, Ruiru; Zhang, Dale (Frontiers in Plant Science, 2025)
The Glu-D1 locus is known to contribute the most to gluten quality in common wheat. Aegilops tauschii, as a donor species of the common wheat D genome, is of great significance for improving wheat flour processing quality by exploring and utilizing its excellent quality-related genes. In this study, high-molecular-weight glutenin subunit (HMW-GS) compositions of 173 Aegilops tauschii accessions from the Middle East, Central Asia, and Xinjiang were analyzed using sodium dodecyl sulfate–polyacrylamide gel electrophoresis (SDS-PAGE) technology. A total of 13 subunit types were detected at the Glu-D1 t locus, including the unique subunit types absent in common wheat. Unexpectedly, all these Ae. tauschii accessions lacked the extra cysteine residue at position 118 in their Glu-1Dx subunits detected by a specific functional marker, dCAPS5. To determine whether other sites of Glu-D1t subunits in Ae. tauschii contains the extra cysteine residue, the grain RNA of Ae. tauschii accessions with rare subunit types at different days post-anthesis (6th, 9th, 12th, 15th, 18th, 21st, and 24th days) were mixed and sequenced using third-generation (PacBio) transcriptome sequencing technology. A total of 12 new HMW-GS genes were obtained, including 6 genes each for Glu-D1x and Glu-D1y. Sequence alignment analysis revealed the extra cysteine residue was not observed in the protein sequences deduced by 12 new HMW-GS genes. Interestingly, HMW-GS of Ae. tauschii accessions AY16 and AY49 had longer repetitive domain insertions, while those of AY16 and AY53 exhibited higher α-helix and β-strand contents, which may positively influence dough properties. Additionally, the relative content of HMW-GS in AY11, AY32, and AY49 was significantly higher than that of the Glu-D1 subunits in wheat variety Xinmai 26 with the strong gluten quality, favoring the formation of larger glutenin polymers. From this point of view, Ae. tauschii, as a potentially valuable germplasm resource, can provide rich subunit gene resources for quality breeding in common wheat.